0457 Sleep-Disordered Breathing Events and Posttraumatic Stress Disorder. (27th April 2018) - Anderson, M; Lavela, J; Mellman, T
Abstract: Introduction: Sleep complaints are a central symptom of PTSD. Fragmented or reduced rapid eye movement sleep (REMS), has been observed early during the course of PTSD. There is accumulating evidence supporting a role for REM sleep in adaptive emotional processing. Sleep-disordered breathing (SDB) has been observed to be common with PTSD. SDB could both contribute to, as well as be a consequence of, disrupted sleep, particularly REMS in PTSD. The purpose of this study was to investigate associations between specific types of SDB events and sleep stages with PTSD. Methods: 51 African American participants (ages 18–35) were selected from a larger study based on adequate sleep evaluation and matching the study groups: current PTSD (n = 17), trauma positive (met criteria for a criterion A trauma but not for full PTSD diagnosis, n = 17), and no previous trauma (n = 17). PTSD criteria were evaluated by the Clinician Administered PTSD Scale and severity was additionally measured with PTSD Checklist (PCL). Each participant had overnight polysomnography (PSG) recordings, which were scored according to the American Academy of Sleep Medicine's guidelines with full respiratory monitoring of the first night. Results: We found a significant correlation between PTSD symptom severity and overall SDB events ( r = .29, p < .05). Poisson regression of count data for specific breathing events revealed fewer hypopneas for the trauma positive group compared to the current PTSD group (exp(β) = .816, p = .016). In the PTSD group, fewer arousals with apneas featured oxygen desaturation throughout the night and in REM, compared to the trauma negative group (exp(β) = 2.64, p = .005; exp(β) = 13.30, p = .012, respectively). Conclusion: These findings raises the possibility that factors in addition to respiration contribute to apnea/arousals in PTSD. Support (If Any): 3UL1TR001409 for the Georgetown Howard Center for Clinical and Translational Research and R01HL087995 to Dr. Mellman.